Intestinal Barrier, Permeability and Nonspecific Inflammation in Functional Gastrointestinal Disorders - A. L. Kovaleva; E. A. Poluektova; O. S. Shifrin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of review. Description of intestinal mucosal barrier permeability disruption causes as morbid factors in gastrointestinal tract (GIT) functional disorders.General provisions. Intestinal mucosal barrier is composed of several elements: pre-epithelial barrier, a mucosal lining of epithelium; epithelial barrier that leverages tight junctional structures and high regenerative capacity of epithelium; post-epithelial barrier established by immune cells and blood vessels. Gut microbiota profile may also be constituent of the intestinal mucosal barrier. Functional dyspepsia (FD) and irritable bowel syndrome (IBS) leave distinct morphological imprint. For instance, FD patients exhibit variant expression of cell junction proteins (claudin-1, zonula occludens, occludin, E-cadherin, β-catenin and desmoglein-2), and IBS patients — overexpression of claudin-2. Permeability disruption leads to inflammatory changes in intestinal wall resulting in visceral and central sensitisation, as well as intestinal motor dysfunctions causal of IBS and FD.Conclusion. Disruption of intestinal mucosal barrier may be considered a pathogenetic factor of PD and IBS progression.